ENFORCEMENT STATUS OF THE POISON ACT 1952 AGAINST OFFENCES RELATED TO KRATOM (MITRAGYNA SPECIOSA KORTH) MISUSE IN MALAYSIA (UUM Journal of Legal Studies, 2020)
Kratom story in Malaysia is a bit intricate. Kratom (Mitragyna speciosa Korth) or local name ketum is a local plant where â€˜mitragynineâ€™ (alkaloid in kratom leaves) is listed as psychotropic substances under the Malaysian Poison Act 1952. The law stated that any activities related to possessing, selling, using, transporting, processing, importing, exporting of kratom are considered illegal and can be prosecuted.  Interestingly, kratom trees are not illegal plant and no laws in Malaysia forbid the cultivation or presence of naturally growing kratom. On the prosecution side, the current laws do little to prosecute kratom addicts for rehabilitation due to no available kratom test kits which can assist the enforcement agency to arrest and prosecute kratom addicts. Therefore, the enforcement of law on kratom has been largely applied for transporting, processing and selling. Though the Poison Act cannot stop anyone who wants to plant or grow kratom there are land laws that prohibit the plantation of kratom on land specified for agriculture purpose, adding tricky situation to the present circumstances of kratom. In pharmacology, there is research and development demand for kratom, and demands from international pharmaceutical companies for kratom had created illegal rational economic exploitation of Malaysiaâ€™s kratom by individuals, so to speak resulting in more intricacies to existing complication. This paper intends to discuss the legal status of kratom in Malaysia which we believe is facing its cross-road. The paper uses the rational approach of economic and criminology arguments to establish kratom offences in the northern states of Malaysia, thus to offer a review to the current state-of-affair.  A police statistics and data on kratom offences are then presented to discuss current status and its implication.Keywords: Enforcement, Kratom (Mitragyna speciosa Korth), kratom offences, Poison Act, Malaysia.